Cloning and Functional Analysis of MADS-box Genes, TaAG-A and TaAG-B, from a Wheat K-type Cytoplasmic Male Sterile Line - Yang, Wenlong; Lou, Xueyuan; Li, Juan; Pu, Mingyu; Mirbahar, Ameer A.; Liu, Dongcheng; Sun, Jiazhu; Zhan, Kehui; He, Lixiong; Zhang, Aimin (Frontiers in Plant Science, 2017)
Wheat (Triticum aestivum L.) is a major crop worldwide. The utilization of heterosis is a promising approach to improve the yield and quality of wheat. Although there have been many studies on wheat cytoplasmic male sterility, its mechanism remains unclear. In this study, we identified two MADS-box genes from a wheat K-type cytoplasmic male sterile (CMS) line using homology-based cloning. These genes were localized on wheat chromosomes 3A and 3B and named TaAG-A and TaAG-B, respectively. Analysis of TaAG-A and TaAG-B expression patterns in leaves, spikes, roots, and stems of Chinese Spring wheat determined using quantitative RT-PCR revealed different expression levels in different tissues. TaAG-A had relatively high expression levels in leaves and spikes, but low levels in roots, while TaAG-B had relatively high expression levels in spikes and lower expression in roots, stems, and leaves. Both genes showed downregulation during the mononucleate to trinucleate stages of pollen development in the maintainer line. In contrast, upregulation of TaAG-B was observed in the CMS line. The transcript levels of the two genes were clearly higher in the CMS line compared to the maintainer line at the trinucleate stage. Overexpression of TaAG-A and TaAG-B in Arabidopsis resulted in phenotypes with earlier reproductive development, premature mortality, and abnormal buds, stamens, and stigmas. Overexpression of TaAG-A and TaAG-B gives rise to mutants with many deformities. Silencing TaAG-A and TaAG-B in a fertile wheat line using the virus-induced gene silencing (VIGS) method resulted in plants with green and yellow striped leaves, emaciated spikes, and decreased selfing seed set rates. These results demonstrate that TaAG-A and TaAG-B may play a role in male sterility in the wheat CMS line.